Hotspots for Initiation of Meiotic Recombination - Tock, Andrew J.; Henderson, Ian R. (Frontiers in Genetics, 2018)
Homologous chromosomes must pair and recombine to ensure faithful chromosome segregation during meiosis, a specialized type of cell division that occurs in sexually reproducing eukaryotes. Meiotic recombination initiates by programmed induction of DNA double-strand breaks (DSBs) by the conserved type II topoisomerase-like enzyme SPO11. A subset of meiotic DSBs are resolved as crossovers, whereby reciprocal exchange of DNA occurs between homologous chromosomes. Importantly, DSBs are non-randomly distributed along eukaryotic chromosomes, forming preferentially in permissive regions known as hotspots. In many species, including plants, DSB hotspots are located within nucleosome-depleted regions. DSB localization is governed by interconnected factors, including cis-regulatory elements, transcription factor binding, and chromatin accessibility, as well as by higher-order chromosome architecture. The spatiotemporal control of DSB formation occurs within a specialized chromosomal structure characterized by sister chromatids organized into linear arrays of chromatin loops that are anchored to a proteinaceous axis. Although SPO11 and its partner proteins required for DSB formation are bound to the axis, DSBs occur preferentially within the chromatin loops, which supports the “tethered-loop/axis model” for meiotic recombination. In this mini review, we discuss insights gained from recent efforts to define and profile DSB hotspots at high resolution in eukaryotic genomes. These advances are deepening our understanding of how meiotic recombination shapes genetic diversity and genome evolution in diverse species.